Circulating tumor cells in newly diagnosed inflammatory breast cancer. Issue 1 (December 2015) - Mego, Michal; Giordano, Antonio; De Giorgi, Ugo; Masuda, Hiroko; Hsu, Limin; Giuliano, Mario; Fouad, Tamer; Dawood, Shaheenah; Ueno, Naoto; Valero, Vicente; Andreopoulou, Eleni; Alvarez, Ricardo; et al.
Abstract Introduction Circulating tumor cells (CTCs) are an independent prognostic factor for progression-free survival (PFS) and overall survival (OS) in patients with metastatic breast cancer. Inflammatory breast cancer (IBC) is one of the most aggressive forms of breast cancer. The prognostic value of a CTC count in newly diagnosed IBC has not been established. The aim of this study was to assess the prognostic value of a baseline CTC count in patients with newly diagnosed IBC. Methods This retrospective study included 147 patients with newly diagnosed IBC (77 with locally advanced and 70 with metastatic IBC) treated with neoadjuvant therapy or first-line chemotherapy during the period from January 2004 through December 2012 at The University of Texas MD Anderson Cancer Center. CTCs were detected and enumerated by using the CellSearch system before patients were started with chemotherapy. Results The proportion of patients with ≥1 CTC was lower among patients with stage III than among patients with metastatic IBC (54.5% versus 84.3%;P = 0.0002); the proportion of patients with ≥5 CTCs was also lower for stage III than for metastatic IBC (19.5% versus 47.1%;P = 0.0004). Patients with fewer than five CTCs had significantly better progression-free survival (PFS) (hazard ratio (HR) = 0.60;P = 0.02) and overall survival (HR = 0.59;P = 0.03) than patients with five or more CTCs. Among patients with stage III IBC, there was a nonsignificant difference in PFS (HR = 0.66; 95% confidence interval (CI), 0.31 to 1.39;P = 0.29) and OS (HR = 0.54; 95% CI, 0.24 to 1.26;P = 0.48) in patients with no CTCs compared with patients with one or more CTCs. In multivariate analysis, CTC was prognostic for PFS and OS independent of clinical stage. Conclusions CTCs can be detected in a large proportion of patients with newly diagnosed IBC and are a strong predictor of worse prognosis in patients with newly diagnosed IBC.